Measuring income-related inequalities in risky health prospects - Gustav Kjellsson; Dennis Petrie; Tom Van Ourti (Tinbergen Institute, 2018)
The measurement of health disparities is a key component for the assessment of health systems. One aspect of these disparities – which hitherto has received limited attention – is the risk people face about their future health. This paper integrates risk into the standard inequality measurement which measures the extent to which disparities in realized health are systematically associated with income. It develops a rank dependent inequality index that considers not only inequalities in expected future health but also the dispersion of individuals' future health prospects. It is useful when a social planner wants to account for risk averse preferences in the assessment of income-related health inequalities. The empirical application using Australian longitudinal data highlights that neglecting risk underestimates income-related health inequalities since the poor were not only expected to be in worse health in the future, but also faced greater dispersion in their future health prospects compared to the rich.
Keywords: D63; I10; 330; health inequality; risk; concentration index